Islamic And Conventional Banks In Qatar: Can Technology Bridge The Gap There? (Journal of Namibian Studies : History Politics Culture, 2023)
As we all know, there are fundamental differences between Islamic banks and conventional banks in the principles, product bases, product types, types of contracts, risk and liability types, and types of activities on which banks can operate. But this article tries to go beyond all this difference to ask for more collaboration in the fintech area to create more customer satisfaction, more harmonization, and a more convenient experience for the customers of both banks. Alongside the digital transformation in payment, seamless access to a wide range of services, including digital payments, online transactions, and mobile banking, led to greater financial inclusion. A better understanding of the data will lead to more development in the field. And over time, that will reduce the cost and enhance effectiveness and efficiency at the operational level.The article assesses the revolutionary potential of technology in bridging the gap between Islamic and conventional finance through a review of the existing situation, including fundamentals, legal frameworks, and market developments. It draws attention to some of the major areas where technology can help this convergence happen, including digital banking options, automated compliance systems, and Shariah-compliant investing platforms.The paper also examines how beneficial such convergence may be for Qatar's economy. It analyzes how a tighter fusion of Islamic and conventional finance might promote financial inclusion, draw foreign capital, and strengthen Qatar's economy globally. The article also discusses the difficulties that could arise from this integration, including complex fundamental issues, regulatory issues, and cultural factors.A qualitative method used with a descriptive approach, a focus group from CEOs of banks and fintech companies, professors, researchers, and students, was created in the CIEF Center to discuss more ideas aboutfintech in Qatar and its impact on the economy. Bridge the Gap was a small title inside the whole discussion, which is why I focused on it in this article to discuss all the ways to bridge the gap so Qatar's economy will benefit.The result of the article is that it endorses the increased merging of technology, which can facilitate innovative financial solutions applicable to both Islamic and conventional institutions.Which will lead to enhanced collaboration, product innovation, and operational efficiencies if the two financial systems converge. Another point is that technology can improve the quality and accessibility of financial services provided by conventional and Islamic banks. Digital banking platforms, smartphone applications, and online services tailored to the consumers of both financial systems may be required. Thirdly, greater productivity and reduced operational costs brought on by the introduction of new technology This could increase customer and bank efficiency, speed, and cost.